Melalui Lensa Ketuhanan: Integrasi Kinerja Keuangan dan Maqasid al-Shariah dalam Perbankan Syariah - Sutihat; Bambang Agus Pramuka (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
This study examines the impact of financial performance and maqasid al-shariah realization on the firm value of 12 Islamic commercial banks in Indonesia from 2016 to 2022, with a total of 84 observations. Using panel data regression and secondary data from audited reports and sustainability disclosures, the findings reveal that the Capital Adequacy Ratio (CAR) negatively and significantly affects firm value, while Return on Assets (ROA) shows no significant effect. Both Non-Performing Financing (NPF) and the Operating Expense to Operating Income ratio (BOPO) have a significant negative impact. Meanwhile, maqasid al-shariah realization does not significantly influence firm value. These results suggest that in Islamic banking, firm value is more closely linked to operational efficiency and financing risk management than to capital adequacy, profitability, or maqasid compliance. The findings align with Quranic principles, Stakeholder Theory, and maqasid al-shariah theory, highlighting justice, efficiency, and social responsibility. This study provides strategic insights to strengthen governance and develop value-based policies for a more sustainable Islamic financial ecosystem.